Food Security in Iceland - Bailes, Alyson J.K., 1949-; Orri Jóhannsson 1979- (2011)
Erindi og greinar The concept of food security applies in both poor and rich societies and concerns the steady availability of food in the right quantity and quality, at the right price. Globally, policies to assure it remain confused and world food prices are rising. Despite large exports of fish, Iceland produces only around half of its inhabitants’ nutritional needs and relies significantly on imports, also for food production inputs like fodder and seeds. Icelandic supplies are affected by oligopoly in the retail market, and could be put at risk by events in other security dimensions ranging from natural disasters and infrastructure failures to terrorism, neighbouring conflicts and other people’s shortages. Icelandic farmers have used the terminology of ‘food security’ to press their claims for more home-grown production, and more recently also in their campaign against EU membership. The general public however shows little sign of security-awareness in this field. The government possesses suitable non-military security frameworks to address food-related risks and has initiated useful, general and specific, studies. Yet it has not developed a strategy or contingency plan for food security, even following the lessons of the 2008 economic crash and 2010-2011 eruptions. Suitable remedies would include larger emergency stocks and a range of measures to reduce vulnerability and improve resilience in crises. Above all, Iceland needs a balanced and open policy-making process to decide what its general future strategy should be as a food-producing and -importing nation. Food security could then be more precisely defined and pursued with the aim of minimizing threats and risks to that agreed vision.